A comparison of the effects of lung protective ventilation and conventional ventilation on the occurrence of atelectasis during laparoscopic surgery in young infants: a randomized controlled trial - Yue, Kun; Wang, Jingru; Wu, Huangxing; Sun, Yingying; Xia, Yin; Chen, Qi (Frontiers in Medicine, 2024)
Objective: This study utilized lung ultrasound to investigate whether lung protective ventilation reduces pulmonary atelectasis and improves intraoperative oxygenation in infants undergoing laparoscopic surgery. Methods: Eighty young infants (aged 1-6 months) who received general anaesthesia for more than 2 hours during laparoscopic surgery were randomized into the lung protective ventilation group (LPV group) and the conventional ventilation group (control group). The LPV group received mechanical ventilation starting at 6 ml/kg tidal volume, 5 cmH2O PEEP, 60% inspired oxygen fraction, and half-hourly alveolar recruitment maneuvers. Control group ventilation began with 8-10 ml/kg tidal volume, 0 cmH2O PEEP, and 60% inspired oxygen fraction. Lung ultrasound was conducted five times-T1 (5 minutes post-intubation), T2 (5 minutes post-pneumoperitoneum), T3 (at the end of surgery), T4 (post-extubation), and T5 (prior to discharge from the PACU)-for each infant. Simultaneous arterial blood gas analysis was performed at T1, T2, T3, and T4. Results: Statistically significant differences were observed in pulmonary atelectasis incidence, lung ultrasound scores, and the PaO2, PaCO2, PaO2/FiO2 ratios at T2, T3, and T4. However, at T5, no statistically significant differences were noted in terms of lung ultrasound scores (4.30±1.87 vs. 5.00±2.43, 95% CI: -1.67 to 0.27, P=0.153) or the incidence of pulmonary atelectasis (32.5% vs. 47.5%, P = 0.171). Conclusions: In infants aged 1-6 months, lung protective ventilation during laparoscopy under general anaesthesia significantly reduced the incidence of pulmonary atelectasis and enhanced intraoperative oxygenation and dynamic lung compliance compared to conventional ventilation. However, these benefits did not persist; no differences were observed in lung ultrasound scores or the incidence of pulmonary atelectasis at PACU discharge. This study was registered at http://www.chictr.org.cn/(trial number: ChiCTR2200058653; April 13, 2022).